2008
DOI: 10.1080/10826080701204854
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peers in the Initiation and Continuation of Ecstasy Use

Abstract: This study is a supplement to the Netherlands XTC Toxicity Study (NeXT), funded by grants from the Netherlands Organisation for Health Research and Development as part of its Addiction Programme. To better understand the processes of peer influence and peer selection, in a field study 106 Ecstasy users (67M/39F, average age 25.4 years) were interviewed face-to-face in Amsterdam in 2005. In the initiation of Ecstasy use, peer influence emerged as the dominating mechanism; peer selection was uncommon. In the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…The results presented here support previously published findings that indicate peer substance use is a strong predictor of future use (Aziz & Shah, 1995;Cruz, Emery, & Turkheimer, 2012;Eitle, 2005;Hussong, 2002;Nakhaee & Jadidi, 2009;Pollard et al, 2010;Tang & Orwin, 2009;Vervaeke, et al 2008), as increased exposure to substance using peers leads to greater likelihood of initiation of use and greater use durations and frequency. No significant findings emerged when considering family history of substance use, likely due to sample homogeneity-all but three participants had drug-using family members.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results presented here support previously published findings that indicate peer substance use is a strong predictor of future use (Aziz & Shah, 1995;Cruz, Emery, & Turkheimer, 2012;Eitle, 2005;Hussong, 2002;Nakhaee & Jadidi, 2009;Pollard et al, 2010;Tang & Orwin, 2009;Vervaeke, et al 2008), as increased exposure to substance using peers leads to greater likelihood of initiation of use and greater use durations and frequency. No significant findings emerged when considering family history of substance use, likely due to sample homogeneity-all but three participants had drug-using family members.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that consider sociocultural factors indicate age at onset of use, the length of time an adolescent uses, and frequency of use are all significantly correlated with future substance use (McNamee, Dunfee, Clark, Eddy, & Tarter, 2008;Oxford, Harachi, Catalano, & Abbott, 2000;Degenhardt et al, 2010;Steinberg, Fletcher, & Darling, 1994). These timing considerations are likely rooted in social processes-studies have confirmed the strongest predictor of on-going substance use is the presence of substance-using peers (Nakhaee & Jadidi, 2009;Piehler, Véronneau, & Dishion, 2012;Pollard, Tucker, Green, Kennedy, & Go, 2010;Vervaeke, Van Deursen, & Korf, 2008). Further, the most common source of opioid access for adolescents are friends and family members (Frese & Eiden, 2011;McCabe, West, & Boyd, 2013), and some research indicates that the majority (up to 70%) of youth gain access to opioids in the home (Brands, Paglia-Boak, Sproule, Leslie, & Adlaf, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Resistance to peer influence in general, and presumably overt peer pressure in particular, increases with age (Steinberg & Monahan, 2007). Moreover, a study on the role of peers in ecstasy use showed that, while peer influence was a dominating mechanism in the initiation of use, it played a lesser role in the continuation of use (Vervaeke, Van Deursen, & Korf, 2008). Although the item 'Because my friends pressure me to' showed high factor loading in Simons' study,modest factor loadings (.46 and .41) were reported in the evaluation studies among slightly older and more frequent users (Chabrol et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have found an association between higher frequency of EDM event attendance and ecstasy use (Abrahamsson & Hakansson, 2013), and a recent study found that regular EDM attendance was associated with three times the odds for high levels of use, and that knowing more than ten ecstasy users was associated with more than double the odds for high levels of use (Smirnov, Najman, Hayatbakhsh, Plotnikova, et al, 2013). Increased risk may be due, in part, to stronger affiliation with drug scenes as previous research has found that ecstasy use is associated with peers and close friends who also use, and offers to try the drug (Ter Bogt & Engels, 2005; Martins, Storr, Alexandre, & Chilcoat, 2008a, 2008b; Smirnov, Najman, Legosz, Wells, & Kemp, 2013; Smirnov, Najman, Hayatbakhsh, Wells, et al, 2013; Vervaeke, Benschop, van den Brink, & Korf, 2008; Vervaeke, van Deursen, & Korf, 2008). Our findings add to these previous studies as we confirmed that high levels of reported exposure to ecstasy users are positively and robustly associated with reporting ecstasy use in these nightclub and festival scenes, even when controlling for all other covariates.…”
Section: Discussionmentioning
confidence: 99%